Bookmarklet-triggered unified literature sharing services in the cloud. (1st January 2014) - Ma, Kun; Zhang, Lei
Currently, modern researchers need convenient approaches and tools for sharing the literature that is available to them. For the purpose of simplifying the literature sharing and elaborating the dynamic role of the human being, we introduce a Bookmarklet-Triggered Unified Literature Sharing Services (BULSS) in the cloud. After clicking the bookmarklet, the sidebar is displayed on the web. In this system, the related literature is pushed to the researchers automatically. The methodology to design the sidebar client, cloud process engine and bookmarklet is presented. Besides, the architectural details of the components are described. This system allows easy manipulation of the literature sharing and academic exchange, which are used frequently and are very often necessary in scientific activity such as research, writing papers and dissertations and preparing reports.